Study on wax deposition of heavy crude oil in pipeline transportation by using oil in water emulsion method - Nor Salwani, Ismail (2013)
Oil in water emulsion occurs in conventional crude oil transportation process. The emulsion stability results from the high concentration of asphaltene, wax, resins and napthenic acid on the composition of emulsion will causing the appearances of wax deposited on the wall of the pipelines, this condition increasing the viscosity of the crude oil emulsion and the pipeline damage and causing problem to the pipeline transportation. In this study the oil in water emulsion was prepared by mixing of the different volume ratio of oil and water. By using the different concentration of surfactant, different speed of mixing and different temperature of mixing, the stability of the condition will be tested. Instead of stability and the viscosity, the shear rate, shear stress, and its density were determined by Brookfield viscometer. The demulsification is also being applied on this study to study the best demulsifier to break the emulsion. It is expected that, the most stable emulsion is that with higher concentration of surfactant, highest speed and the higher volume of the oil. By increasing the mixing speed, lowering temperature and increasing time of speed results increasing the viscosity of the emulsions.